The use of tensiomyography in older adults: a systematic review - Pus, Katarina; Paravlic, Armin H.; Šimunič, Boštjan (Frontiers in Physiology, 2023)
Introduction: Aging of skeletal muscles results in a cascade of events negatively affecting muscle mass, strength, and function, leading to reduced mobility, increased risk of falls, disability, and loss of independence. To date, different methods are used to assess muscle mechanical function, tensiomyography (TMG) being one of them. The aim of this review was twofold: to summarize the evidence-based usefulness of tensiomyography in older adults and to establish reference values for the main tensiomyography parameters in older adults. Methods: The PubMed, Web of Science, SPORTDiscus, and tensiomyography databases were searched from inception until 25 December 2022. Studies investigating older adults (aged 60+ years) that reported tensiomyography-derived parameters such as contraction time (Tc) and/or maximal displacement (Dm) were included. Methodological quality was assessed using the Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Results: In total, eight studies satisfied the inclusion criteria. Tensiomyography has been used on different groups of older adults, including asymptomatic, master athletes, patients with peripheral arterial disease, and patients with end-stage knee osteoarthritis with a mean age of 71.5 ± 5.38 (55.7% male subjects). The most evaluated were leg muscles such as vastus lateralis (VL), gastrocnemius medialis (GM), and biceps femoris (BF). The present review demonstrates that tensiomyography is used to assess neuromuscular function in asymptomatic and diseased older adults. When compared to asymptomatic individuals, power master athletes, knee osteoarthritis patients, and patients diagnosed with peripheral arterial disease have the shortest Tc in BF, VL, and GM muscles, respectively. On the other hand, endurance master athletes showed the longest Tc in all three evaluated muscles. Less mobile, nursing-home residents showed higher Dm in VL and BF, while lower Dm in GM than the asymptomatic group. The knee osteoarthritis group showed the largest Dm in BF and VL while having the smallest Dm in GM. Conclusion: Tensiomyography can serve as a valuable tool for assessing neuromuscular function in older adults. The method is sensitive to muscle composition, architecture, and (pre) atrophic changes of the skeletal muscles and might be responsive to muscle quality changes in aging and diseased populations. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=402345, identifier CRD42023402345.